Pengaruh Kualitas Pelayanan, Kualitas Produk, Dan Harga Terhadap Loyalitas Pelanggan Pada Toko Rini Cosmetic Dengan Kepuasan Pelanggan Sebagai Variabel Intervening - Reni Setawati; Nani Septiana; Sugeng (Universitas Muhammadiyah Metro, 2025)
This research was conducted at the Rini Cosmetics Shop. This research is quantitative byinterpreting the independent and dependent variables. This study aims to determine the effectof service quality, product quality, and price on customer loyalty and customer satisfaction atRini Cosmetic store customers by using 50 respondents as a research sample and thesampling technique using accidental sampling. The data analysis method used is aquantitative analysis method including validity test, reliability test, normality test, linearitytest and regression significance, homogeneity test, hypothesis requirements and statisticalhypotheses. Data analysis in this study used path analysis (Path) with the help of the SPSSversion 25.0 application. The results of the study indicate that there is a direct influencebetween service quality and customer satisfaction at Rini cosmetic shops. There is a directeffect of product quality on customer satisfaction at Rini Cosmetics stores. There is a directeffect of price on customer satisfaction at Rini Cosmetic stores. There is a direct effect ofservice quality on customer loyalty to Rini Cosmetic stores. There is an effect of productquality on customer loyalty to Rini Cosmetic stores. There is an effect of price on customerloyalty to Rini Cosmetic stores. There is a direct effect of customer satisfaction on customerloyalty to Rini Cosmetic Stores